My professor said the following in his lecture:

Suppose $M$ and $P$ are free modules and $\alpha: M\rightarrow P$ is a surjection. Then $\alpha$ splits and the kernel of $\alpha$ is a summand of $M$.

I know that $M$ and $P$ being free means that they have a basis and hence, any element can be written as a linear combo of the basis elements. I also know that if $\alpha$ being split means that there exists a $\beta: P\rightarrow M$ such that $\alpha\beta=1_{P}$. I am having trouble understanding why this surjection of free modules implies that the surjection splits. How do I get started?

  • 2
    $\begingroup$ Really this is because $P$ is projective, but it's even easier when it's free. Since $P$ is free we have a basis, so I can define a module homomorphism $P\to M$ just by sending the basis of $P$ wherever I want. So I can send the basis elements of $P$ to preimages under $\alpha$ since $\alpha$ is surjective. $\endgroup$
    – Dave
    Feb 7 '21 at 23:36

The key property of the free module $F$ with basis $\{f_i\}_{i\in I}$ is the following:

For every module $N$ and every choice of elements $n_i\in N$, $i\in I$, there exists a unique module homomorphism $\phi\colon F\to N$ such that $\phi(f_i)=n_i$.

Let $\{p_i\}_{i\in I}$ be a basis for $P$. For each $i$, there exists $m_i\in M$ such that $\alpha(m_i)=p_i$. Define $\beta$ to be the (unique) morphism induced by mapping $\beta(p_i)=m_i$. Then $\alpha\beta(p_i) = \alpha(m_i)=p_i$. Thus, $\alpha\beta$ is the identity on the basis, hence is the identity morphism.

Now let $A=\mathrm{ker}(\alpha)$, and $B=\mathrm{Im}(\beta)$. If $x\in A\cap B$, then $x=\beta(p)$ for some $p\in P$, hence $0 = \alpha(x) = \alpha\beta(p) = p$. Thus, $x=\beta(p)=\beta(0)=0$, so $A\cap B=\{0\}$. And if $m\in M$, then $\beta(\alpha(m))\in B$, and $m-\beta(\alpha(m))\in A$, with $m=\beta(\alpha(m)) + (m-\beta(\alpha(m))$, proving that $A+B=M$. Thus, $M=A\oplus B$.

Note the last part does not use the facts that $M$ and $P$ are free. In general, if $N$ and $N’$ are any modules, and $\alpha\colon N\to N’$ splits (has a right inverse), then $\mathrm{ker}(\alpha)$ is a direct summand of $N$, and $N$ is isomorphic to a direct sum $N’\oplus N’’$.

The first part shows that free modules are projective. A module $P$ is projective if and only if, for every pair of modules $M$ and $M’$, and surjective module morphism $f\colon M\to M’$, if there is a morphism $\alpha\colon P\to M’$, then there is a morphism $\beta\colon P\to M$ such that $f\beta=\alpha$. That is: if you have a diagram $$\begin{array}{ccccc} && P \\ &&\downarrow\alpha\\ M&\stackrel{f}{\longrightarrow}&M’&\rightarrow &0 \end{array}$$ with bottom row exact, then there exists a morphism $\beta$ such that $$\begin{array}{ccccc} && P \\ &{\scriptstyle\beta}\swarrow&\downarrow\alpha\\ M&\stackrel{f}{\longrightarrow}&M’&\rightarrow &0 \end{array}$$ that makes the diagram commutative.

Free modules are always projective, and for some rings, projective modules are necessarily free; but for other rings, you may have projective modules that are not free. A module is projective if and only if it is a direct summand of a free module.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.